Absicherung von Strompreisrisiken mit Futures: Theorie und Empirie - Marc Rodt; Klaus Schäfer (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2005)
The regulatory changes in the german electric power market result in rising electricity price volatility. As a consequence electricity price risk management is essential for an electricity trader. The paper therefore analyzes the needed volume of futures hedging for an electricity trader, that ist tries to derive the optimal hedge ratio. In the first step the theoretical conditions for a preference-free optimal hedge ratio are discussed. In the second step these conditions are analyzed empirically with data for the german electricity exchange EEX and the scandinavian electricity exchange Nord Pool.
Keywords: C10; G13; Q40; 330; Electricity Price Risk; Electricity Futures; optimal Hedge Ratio